Pharmacological Effects of Carvacrol in In vitro Studies: A Review - Silva, Erika R.; de Carvalho, Fernanda Oliveira; Teixeira, Luciana G. B.; Santos, Nayara Gomes Lima; Felipe, Fernanda Araújo; Santana, Hericalizandra Santa Rosa; Shanmugam, Saranavan; Quintans Júnior, Lucindo José; de Souza Araújo, Adriano Antunes; Nunes, Paula Santos (Current Pharmaceutical Design, 2018)
Carvacrol has a high therapeutic potential, with in vitro studies showing promising results in different cellular models using a variety of methodological designs. Therefore, the objective of this study was to conduct a systematic review to analyze the pharmacological effects of carvacrol in in vitro studies. A comprehensive search of the literature was made using four databases: Science Direct, Scopus, MEDLINE-PubMed, and Web of Science using different combinations of the following keywords: carvacrol, drug therapy, therapeutic uses, in vitro study. The search of the databases was for studies conducted in the period up to and including September 2016. A total of 3,269 studies were initially identified, with only 31 meeting the inclusion criteria. The included studies contained a variety of in vitro models able to determine the properties of Carvacrol. The following properties of Carvacrol were identified: antimicrobial (7 studies), bactericidal (4), bactericidal and antifungal (1), antiinflammatory (4), anticancer (4), mutagenic (4), antioxidant (3), antifungal (3), antidepressant (1), as a modulator of nerve impulses (1) and an immunological modulator (1). The In vitro studies with Carvacrol included in this review showed a diversity of models and confirmed the therapeutic potential of this product in relation to several diseases.
Keywords: natural product